Safer Tractor Operations for Farm Workers/ Employees - Carol J. Lehtola; Charles M. Brown (EDIS)
This publication is one in "Safer Tractor Operations" series, a collection of UF/IFAS Extension circulars and fact sheets devoted to tractor safety for various audiences. . This document is CIR 1254, one of a series of the Agricultural and Biological Engineering Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First published November 2002.